1998
DOI: 10.1002/(sici)1096-9861(19981207)402:1<129::aid-cne9>3.3.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Time‐dependence and cell‐type specificity of synergistic neurotrophin actions on spiral ganglion neurons

Abstract: The neurotrophins brain-derived neurotrophin (BDNF) and neurotrophin-3 (NT-3) synergistically enhance survival of spiral ganglion neurons such that simultaneous exposure to both compounds produces a larger response than would be expected from their individual effects. To elucidate the functional role of this neurotrophin interaction, we examined its temporal and cell-type specificity in vitro for both mouse and gerbil spiral ganglion neurons. Synergistic effects were transient; they were maximal within the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Thus, as with the calretinin and calbindin colabeling pattern in the retina that indicates separate parallel pathways demarked by calcium binding protein distribution (Mojumder et al, ), we wondered whether this was also the case in the spiral ganglion. To explore this possibility further, we took advantage of the type II neuron marker peripherin (Hafidi, ), which has previously been validated to stain type II spiral ganglion neurons specifically (Mou et al, ). Colabeling of peripherin with either calretinin or calbindin was characterized in individual experiments to obtain unequivocal profiles of calretinin and calbindin distributions in type I and type II neurons in vitro.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as with the calretinin and calbindin colabeling pattern in the retina that indicates separate parallel pathways demarked by calcium binding protein distribution (Mojumder et al, ), we wondered whether this was also the case in the spiral ganglion. To explore this possibility further, we took advantage of the type II neuron marker peripherin (Hafidi, ), which has previously been validated to stain type II spiral ganglion neurons specifically (Mou et al, ). Colabeling of peripherin with either calretinin or calbindin was characterized in individual experiments to obtain unequivocal profiles of calretinin and calbindin distributions in type I and type II neurons in vitro.…”
Section: Resultsmentioning
confidence: 99%
“…Monoclonal mouse antiperipherin antibody (Chemicon, Temecula, CA; MAB1527) was used as a marker for type II spiral ganglion neurons according to previous reports (Mou et al, ; Reid et al, ). The appropriate concentration of antiperipherin antibody was determined using a preparation in which the organ of Corti and the ganglion were cultured for 3 days in vitro, such that the type I and type II afferent innervations patterns were retained and could be distinguished by using antiperipherin antibody staining (Flores‐Otero and Davis, ).…”
Section: Methodsmentioning
confidence: 99%
“…Evidence that these neurons might be especially susceptible to developmental cell death is provided by studies of mice and gerbil spiral ganglion cells growing in organotypic cultures. In these experiments, NT-3 and BDNF, two neurotrophic molecules expressed within the developing cochlea, were found to act synergistically in a time-dependent and cell-specific manner to enhance the survival of Type I, but not Type II neurons (Mou et al, 1997(Mou et al, , 1998. These effects were maximal in cochlear explants obtained from animals during the first 2 postnatal days.…”
Section: Time-course Of Cochlear Neuron Cell Deathmentioning
confidence: 86%
“…While recent studies in rats indicate that peripherin is up-regulated in type I SGN following explant culture of P5 SGN [16], it seems that this up-regulation is species specific. Thorough examination of mouse SGN following organotypic and explant culture has shown that peripherin is not up-regulated in type I SGN [23, 27]. While we show a large number of SGN express peripherin in our P1 explants, this likely reflects the relatively larger representation of type II SGN near birth [14] as the number of peripherin immunolabelled neurons in P7 SGN explants reflects the mature representation of type II SGN in the cochlea (M. Barclay, A. F. Ryan and G. D. Housley, unpublished observations).…”
Section: Discussionmentioning
confidence: 99%